Genes adopt non‐optimal codon usage to generate cell cycle‐dependent oscillations in protein levels - Milana Frenkel‐Morgenstern; Tamar Danon; Thomas Christian; Takao Igarashi; Lydia Cohen; Ya‐Ming Hou; Lars Juhl Jensen (Molecular Systems Biology)
Abstract The cell cycle is a temporal program that regulates DNA synthesis and cell division. When we compared the codon usage of cell cycle‐regulated genes with that of other genes, we discovered that there is a significant preference for non‐optimal codons. Moreover, genes encoding proteins that cycle at the protein level exhibit non‐optimal codon preferences. Remarkably, cell cycle‐regulated genes expressed in different phases display different codon preferences. Here, we show empirically that transfer RNA (tRNA) expression is indeed highest in the G2 phase of the cell cycle, consistent with the non‐optimal codon usage of genes expressed at this time, and lowest toward the end of G1, reflecting the optimal codon usage of G1 genes. Accordingly, protein levels of human glycyl‐, threonyl‐, and glutamyl‐prolyl tRNA synthetases were found to oscillate, peaking in G2/M phase. In light of our findings, we propose that non‐optimal (wobbly) matching codons influence protein synthesis during the cell cycle. We describe a new mathematical model that shows how codon usage can give rise to cell‐cycle regulation. In summary, our data indicate that cells exploit wobbling to generate cell cycle‐dependent dynamics of proteins.